MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
Menu
Grade: 11
        
Solve the equation for x : 
log to the base a ( 1 + log to the base b ( 1 + log to the base c ( 1 + log to the base d (x)))) = 0
10 months ago

Answers : (2)

Ram Janam
29 Points
							
take antilog on both sides,which gives... 1 + log to the base b ( 1 + log to the base c ( 1 + log to the base d (x)))= a0.
 log to the base b ( 1 + log to the base c ( 1 + log to the base d (x))) = 0....take antilog again.
  1 + log to the base c ( 1 + log to the base d (x)) = b0.
log to the base c ( 1 + log to the base d (x)) = 0....take antilog again.
1 + log to the base d (x) = c0.
 log to the base d (x) = 0....take antilog again.
x=d0.
x=1....ANS.
REMEMBER...logax=0...on taking antilog it converts to.
x=a0....which gives 
x=1
 
10 months ago
Ram Janam
29 Points
							
loga(1+logb(1+logc(1+log(x)=0
take antilog on both sides..
1+logb(1+logc(1+log(x)=a0
logb(1+logc(1+log(x)=0
take antilog on both sides
1+logc(1+log(x)=b0
logc(1+log(x)=0.
take antilog on both sides
1+log(x)=c0
log(x)=0
take antilog 
x=d0
x=1..ANS
[REMEMBER.........loga b=0...on taking antilog
b=a to the power of 0
b=1]
 
10 months ago
Think You Can Provide A Better Answer ?
Answer & Earn Cool Goodies


Course Features

  • 731 Video Lectures
  • Revision Notes
  • Previous Year Papers
  • Mind Map
  • Study Planner
  • NCERT Solutions
  • Discussion Forum
  • Test paper with Video Solution


Course Features

  • 731 Video Lectures
  • Revision Notes
  • Test paper with Video Solution
  • Mind Map
  • Study Planner
  • NCERT Solutions
  • Discussion Forum
  • Previous Year Exam Questions


Ask Experts

Have any Question? Ask Experts

Post Question

 
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!! Click Here for details